Dye inhibition of phosphate transport in everted duodenal sacs of mice - Mary, Panthalookaren Lonappan; Rao, Jonnakuty Prakasa; Nepal, Ojashwi (Journal of Physiological Society of Nepal, 2020)
Phenol Red has been widely used to test kidney function in man. Using the simple, everted gut sac technique has been observed to inhibit the phosphate transport by phenol red in the mouse intestine. We wanted to see if other similar organic anions are able to inhibit the phosphate transport across the mouse intestine. Both uptake and release of phosphate by the everted duodenal sacs of mice are inhibited by phenol red, bromocresol green and bromophenol blue. At the highest dose all the dyes were able to inhibit both influx and efflux significantly. Loss of phosphate from bathing solution is taken as influx and the gain of phosphate by the solution within the sac is taken efflux. At higher dosages a trend of increase in E/I% was noted. At the highest dose all the dyes were able to increase this parameter significantly over the control. Influx appears to be the primary process to be affected. Possible use of phenol red, on account of its safety in humans, as a hypophosphatemic agent is suggested.